The STAD Learning Model: A Solustion for Improving Akidah Akhlak Learning Outcomes at MTs Darul Ulum Karang Sari - Nirwana Nirwana; Putri Perli Marjusa; Putri Susanti; Nur Hauna; Ningrum Ningrum; Nurul Azizah (PT. Pusmedia Group Indonesia, 2025)
This research is based on the fact that student learning outcomes are still low, which is caused by the use of conventional learning methods that tend not to encourage students' active involvement in the learning process. One alternative that can be used is a cooperative learning model with the type of Student Teams Achievement Division (CITY). This study aims to analyze the impact of the application of the STAD learning model on the achievement of learning outcomes of grade VIII students at MTs Darul Ulum Karang Sari. The research uses a quantitative approach with a quasi-experimental design. This study involved two sample groups: class VIII.3 as an experimental group with the application of the STAD model, and class VIII.1 as a control group that continued to use conventional learning approaches. The instrument used in this study is a test to measure student learning outcomes. Data analysis was carried out using the Mann-Whitney Test, because the data distribution was abnormal and the purpose of the analysis was to compare learning outcomes between two groups of students. The test results showed a significant difference between the two groups, with a significance value of 0.043 (below 0.05). These findings indicate that the application of the STAD learning model is effective in improving student learning outcomes.